From Revelation to Ideology An Epistemological Critique of Hizb ut-Tahrir’s Qur’anic Exegesis - Moh. Alwy Amru Ghozali (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2026)
This article examines Hizbut Tahrir’s political interpretation of the Qur’an as an epistemological problem, rather than merely a theological or political disagreement within Islam. Existing studies on Hizbut Tahrir predominantly adopt descriptive or normative approaches, thereby paying insufficient attention to the structures of knowledge that underlie its interpretive practices. By employing a epistemological analysis of Qur’anic exegesis framework, this study situates Hizbut Tahrir’s tafsīr within broader debates in Qur’anic studies, particularly those concerning the relationship between discourse, power, and knowledge. The analysis focuses on key political verses frequently invoked by Hizbut Tahrir to justify the ideology of the caliphate, demonstrating how meaning is stabilized through literalist and absolutist readings that foreclose interpretive plurality. This process results in a systematic closure of meaning, whereby revelation is transformed from an open ethical horizon into an instrument of ideological legitimation. The findings reveal an epistemic shift from wahy (revelation) as a dynamic source of moral guidance to ideology as a rigid interpretive framework that precedes and governs the text. By foregrounding the discursive and power-laden nature of Qur’anic interpretation, this article contributes to the development of a critical epistemology of tafsīr and underscores the necessity of hermeneutical reflexivity and scholarly accountability in contemporary readings of the Qur’an.